Plants, people, and place: complex, mutualistic, and co-evolving global patterns through time - Van Wijk, Yvette Ethné (Rhodes University, Faculty of Science, Botany Department, 2019)
My thesis studies and analyses the suite of distinctive plant taxa which persist in small patches of vegetation growing in close association with archaeological habitation sites in the southern Cape, South Africa. The unexpected correlation and overlap between botanical taxa collected at 75 site complexes, and ethnobotanical data collected in collaboration with modern Khoi-San communities in the same area, is explored and interrogated. Although sparse, reports of the same suite of taxa recovered from archaeological excavations in the Cape provinces provides depth of time to the study, linking the past to the present. The three-way correlation of a suite of plants closely associated with humans and habitation sites through time, allows for triangulation of the data in order to validate and cross verify the results using more than one frame of reference. Both the plants and the knowledge about their uses have persisted in spite of historical attrition, and alienation of land and language, suffered by the Khoi-San over the past 300 years. Drawing on a large body of primary and secondary data, and using an interdisciplinary, abductive and pragmatic mixed methods approach, a pattern can be traced throughout Africa and globally. Regression analysis strongly indicates that the most ubiquitous taxa were selected for a purpose and are not randomly present in association with humans. Botanical, anthropological, and archaeological studies seldom focus on the inter-connectedness of people and plants at the sites they inhabited. Very little research into modern vegetation in close association with the sites has been undertaken, and vegetation mapping has not captured the occurrence of these site-specific small vegetation patches recorded during my surveys. The topographically, geologically, and vegetatively complex and varied southern Cape, and greater Cape area, is extremely rich in archaeological sites and history. This study suggests that the value of site-specific plant taxa to humans throughout the aeons of pre-agricultural history, persists into the present. Due to tolerance of a broad range of climatic and environmental variables, there is value in the study of these ancient and neglected useful plants in the face of climate change. That this vegetation is so closely associated with archaeological sites of cultural and historic importance confers an urgency to recognising the existence and significance of the distinctive and possibly anthropogenic vegetation surrounding the sites.
Keywords: Ethnobotany -- South Africa -- Western Cape; Khoisan (African people) -- Ethnobotany; Human-plant relationships -- South Africa -- Western Cape; Plants -- Classification -- South Africa -- Western Cape; Plant remains (Archaeology) -- South Africa -- Western Cape; Ethnoscience -- South Africa -- Western Cape; Regression analysis